A Promising Effect of Pravastatin For Reducing Preeclamsia Incidence In High Risk Pregnant Women - Zata, Fariska; Nasir, Mohammad (Jurnal Medis Islam Internasional, 2019)
Preeclamsia is still a threat in obstetrics because it is the leading cause of maternal death (15-20% in developing countries). Globally, preeclampsia causes 70,000-80,000 pregnant women to die and 500,000 babies die annually1, with increased morbidity such as prematurity and fetal growth disturbance2. The exact cause of preeclampsia is still not clearly known (also called "The disease of theory"), but recent studies shows that the imbalance of pro-angiogenic (VEGF, PlGF) and anti-angiogenic factors (sFlt-1, s-Eng) plays an important role in the pathogenesis preeclampsia. The presence of general maternal endothelial dysfunction induced by an imbalance of these factors is a major phenomenon in preeclampsia, which results in placental hypoxia / ischemia, resulting in vasoconstriction resulting in hypertension1. Termination of pregnancy is still as a definitive therapy for preeclamsia. Therefore, early prevention is necessary in the management of preeclampsia. In 2013, ACOG recommended the administration of low-dose aspirin and calcium 1 gram / day to patients in pregnant women with high risk of preeclamsia3. However, low-dose aspirin is less useful in preventing preeclampsia in patients with a history of previous chronic hypertension4 and not reduce the incidence of term preeclampsia (the incidence of preeclampsia at gestational age above 37 weeks)5,6. This weakness of low-dose aspirin has led to recent research focusing on the prevention of preeclampsia. The similarity between the pathogenesis mechanism of preeclampsia and cardiovascular disease makes pravastatin (a protective therapy in cardiovascular disease before) as a potential agent for preventing preeclampsia7. Therefore, the role of pravastatin for reducing preeclampsia incidence in high risk pregnant women will be discussed in this article.